2021
DOI: 10.3758/s13415-021-00893-x
|View full text |Cite
|
Sign up to set email alerts
|

Neural systems underlying the learning of cognitive effort costs

Abstract: People balance the benefits of cognitive work against the costs of cognitive effort. Models that incorporate prospective estimates of the costs of cognitive effort into decision making require a mechanism by which these costs are learned. However, it remains an open question what brain systems are important for this learning, particularly when learning is not tied explicitly to a decision about what task to perform. In this fMRI experiment, we parametrically manipulated the level of effort a task requires by i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…Further, extensive neuroimaging and neurophysiological evidence indicates that ACC is especially sensitive to cognitive effort and fatigue (Engstrom et al, 2015;Massar et al, 2015;Muller & App, 2019;Persson et al, 2013;Shenhev et al, 2017;Vassena et al, 2017). For example, application of transcranial THE CONTROLLOSPHERE brain stimulation over human dorsomedial prefrontal cortex (including ACC) modulates the willingness of subjects to apply mental effort (Soutschek et al, 2022), and ACC prediction errors are associated with learning the costs of cognitive effort (Sayali & Badre, 2021). Notably, an RNN model of ACC predicts upcoming cognitive states based on information about the current state, eliciting prediction errors to unexpected changes in state .…”
Section: Anterior Cingulate Cortexmentioning
confidence: 99%
“…Further, extensive neuroimaging and neurophysiological evidence indicates that ACC is especially sensitive to cognitive effort and fatigue (Engstrom et al, 2015;Massar et al, 2015;Muller & App, 2019;Persson et al, 2013;Shenhev et al, 2017;Vassena et al, 2017). For example, application of transcranial THE CONTROLLOSPHERE brain stimulation over human dorsomedial prefrontal cortex (including ACC) modulates the willingness of subjects to apply mental effort (Soutschek et al, 2022), and ACC prediction errors are associated with learning the costs of cognitive effort (Sayali & Badre, 2021). Notably, an RNN model of ACC predicts upcoming cognitive states based on information about the current state, eliciting prediction errors to unexpected changes in state .…”
Section: Anterior Cingulate Cortexmentioning
confidence: 99%
“…Further, TD learning was reported as the learning algorithm of pain and loss of reward, just as for rewards, although the PE of these positive punishments is thought to be encoded with opposite signs to reward PE signals in the human striatum (Seymour et al ., 2007; Seymour et al ., 2004; Sutton and Barto, 2018). Modeling of behavioural and neural data indicate that mental effort costs respect RL algorithms (Nagase et al ., 2018; Sayali and Badre, 2019; Sayali and Badre, 2021). Collectively, these prior studies imply that human brains learn mental effort cost as an integrated value in the manner of TD learning.…”
Section: Discussionmentioning
confidence: 99%
“…Striatal dopamine dynamics reflect a dissociation between the learning of reward values and physical effort costs (Gan et al, 2010). Although studies have consistently shown that humans avoid mental effort, few have investigated the neural mechanisms by which mental effort costs are learned (Cavanagh et al, 2014; Kool et al, 2010; Nagase et al, 2018; Sayali and Badre, 2019; Sayali and Badre, 2021; Westbrook et al, 2013). Therefore, little is known about what mechanism underlies adaptive learning to avoid mental effort.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations